Critical Review of Habermas’ Communicative Action: Implication on Organizational Leadership - Daguplo, Marvin (JPAIR Multidisciplinary Research, 2013)
An organization is a conglomeration of individual cultural practices and not just a system of human beings acting and interacting with each other (Dy, 1997). This communion can either result to thought conflict or agreement. Presently, conflict is more observed within the organization. In response, this critical action research aimed to situate Habermas’ communicative action among leaders’ role in unifying organizations. Hermeneutic analysis found that Habermas emphasized dialogue and open communication as unifying agents for interpersonal relationship and solidarity within the organization. He clarified that leaders should consider the organization as an integral part of family relationship where every member is heard equally. Moreover, empowerment and encouragement among members of the organization were emphasized as contributory factors to strengthen the organization. Lastly, competent leaders systematically and orderly organized and deliberate things along with the other members in the organization. Hence, leaders’ self-reflection and effective communication provides a better way of social and organizational formation and transformation. Leaders, therefore, must equip themselves with the necessary skills and techniques on communicative administration for the good of the organization. There is a must to change the view of society born from labor into a society which grows from interaction of people living and dreaming together.